Dysecdysis secondary to anaphylactic reaction in a captive royal python {python regius) at the Zoological garden, Ibadan, Nigeria (2016)
Dysecdysis in a royal python is reported. Clinical observation included pruritus, gasping and urticarial rash with massive local circumscribed spontaneous swellings which later developed into moist and inflamed wheals culminating into foci of blisters with extensive skin shedding affecting mostly two third of the hind quarters. Bacteriological examination of blister swabs revealed Escherichia coli and haematology stressed neutrophils, eosinphilia with massive mast cell degranulation. Stressful conditions from captive environment associated with prolong anorexia and the provisioning of a new prey different from those obtained in wild may precipitate immune mediated reactions. This is a rare documentation of dysecdysis with anaphylaxis from a captive facility in Nigeria